Russian linguopolitical personology: political leaders’ discourse - Chudinov, A.P.; Nakhimova, E.A.; Nikiforova, M.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2018)
The paper presents an analytical review of publications devoted to the study of political leaders’ verbal image. The research of politicians’ individual discourses belongs to the sphere of linguopolitical personology, which is a relatively new field of Russian linguistics that focuses on the phenomenon of professional linguistic personality in the sphere of politics. The objectives of the review are to specify basic terminology, which is in use, to determine the most popular methods of analysis and research tasks, and to define the boundaries of the considered research area in the context of modern Humanities. The analysis highlighted two main subject areas of linguopolitical personology: presidential discourse study and historical personalities study. The research of political leaders’ proper names in terms of precedent phenomena is also considered to be a peripheral subject area. Each of the identified research spheres is characterized from the perspective of the goal, methods of analysis to be applied and principles of language material selection. We have grounds to believe that the use of a broad approach in defining research boundaries of linguopolitical personology enables to study a vast language material base and to use various methods of study, which in its turn results in increasing interdisciplinary connections of linguopolitical personology and even broader, of political linguistics, with other fields of modern Humanities. Thus, the identified research areas reflect the perspectives of the modern science and therefore, are to provide a multidimensional, comprehensive analysis of the phenomenon of professional linguistic personality in the field of political communication.